Formulation and Optimization of Controlled Porosity Osmotic Pump Tablet for Oral Administration of Glipizide - Payghan, Dr. Santosh A. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Glipizide (GZ) which is oral hypoglycemic drug belongs to BCS Class II was selected as a model drug to prepare controlled porosity osmotic pump (CPOP) tablet. Materials and Methods: The solubility of GZ was increased by forming its solid dispersion (SD) with polyvinylpyrrolidone (PVP). The GZ–PVP SD (GZ-SD) systems were prepared by physical mixing and spray drying method, and characterized by differential scanning calorimetry, powder X-ray diffraction analysis, Fourier transform-infrared spectroscopy, and scanning electron microscopy (SEM). Results and Discussion: The effect of different formulation variables - such as the level of solubility modifier in the core, membrane weight gain, and level of pore former in the membrane - were studied. Drug release was found to be affected by the level of solubility modifier present in the core. GZ release was inversely proportional to the membrane weight but directly related to the initial level of pore former (PVP, sorbitol) in the membrane. Drug release from the developed formulations was independent of pH and agitational intensity, but dependent on the osmotic pressure of the dissolution media. Conclusion: Results of SEM studies confirmed the formation of pores in the membrane from where the drug release occurred. The formulations were stable after 3 months of accelerated stability studies. The results indicated that CPOP tablet developed using spray dried GZ–SD had excellent zero-order release characteristics in vitro.